«Conflicto patricio y violencia popular en Copiapó durante la guerra civil de 1851» Avances de investigación y propuesta metodológica para el estudio de los motines y revueltas populares - Pérez Silva, Claudio (Revista de Historia Social y de las Mentalidades, 2011)
The main purpose of this essay is to analyze th e violent social demonstrations that took place in popular areas during the political and mil itary conflict of the1851 civil war. This is why we will focus particularly on the mining world of the “small north”, a region characterized by the early appearance of violent so cial conflicts, caused by the economic and social transformations of a traditional society turning into a capitalist one. There is alsoa methodological suggestion to study the violent po pular displays that are characteristic in this part of the country, such as workers mutinies and miners’ uprisings.
Keywords: Popular violence; Social history; Local history